Kawasaki-like illness following COVID-19 infection in a minor ß-thalassemic girl - Trevisan, Giusto (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Multisystem inflammatory syndrome (MIS), also known as a Kawasaki-like illness, is a rare condition linked to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It presents with systemic inflammation and organ dysfunction, and it shares several clinical features with Kawasaki disease (KD). This case report describes an 8-year-old girl that developed symptoms suggestive of MIS or KD several weeks after a COVID-19 infection. She experienced a high fever lasting 4 days, followed by the appearance of itchy, erythematous patches on her legs, which later spread to her trunk and face. The inflammatory symptoms resolved spontaneously in less than 2 months without any lasting effects.
Keywords: children; COVID-19; Kawasakijeva bolezen; Kawasaki-like illness; multisistemski vnetni sindrom; multisystem inflammatory syndrome; otroci; ß-talasemija; ß-thalassemia